Analisis Pengaruh Ketimpangan Pembangunan Dan Pertumbuhan Ekonomi Terhadap Kemiskinan di Kabupaten Mimika - Harlina, Harlina; Manduapessy, Rulan L (STIE Jambatan Bulan, 2023)
This study aims to find out: The effect of development inequality and economic growth on poverty in Mimika Regency. The method used in this study is the associative method. Data collection techniques through documentation. The analytical tool used is multiple linear regression. The results showed that partially development inequality had a positive effect and significance and ecomonic growth had a positive but not significant effect on poverty in Mimika Regency. Meanwhile, in terms of feasibility, the development inequality model and economic growth have a significant effect on poverty in Mimika Regency.